Perbandingan Efisiensi Metode Simple Additive Weighting (SAW) dan Weighted Product (WP) Dalam Sistem Penilaian Kinerja Guru Honorer - Maulana, Romdon; Handayani, Murni; Anggai, Sajarwo (Jurnal Ilmu Komputer, 2024)
The teacher is the key to the success of the quality of education in this country with the main task of educating, teaching, guiding, directing, training, assessing, and evaluating students in early childhood education through formal education, basic education and secondary education. Teachers with honorary teacher status are the beginning of a career path for a teacher. assessment of teacher performance as an illustration of the results of the performance and teaching ability of a teacher. In addition to encouraging motivation, dedication, loyalty, professionalism, and improving the quality of education, teacher performance assessments are also used as a reference, and recommendation for raising the teacher's career path. The methods used in teacher performance assessment research or with similar objects are the SAW method, WP method, Fuzzy Logic, Analytical Hierarchy Process (AHP) method, Decision Tree method, Composite Performance Index (CPI) method and TOPSIS method. However, there has been no research comparing the SAW method with the WP method in terms of the efficiency of the calculation process time, so it is not yet known which method is more efficient in terms of calculation process time in the teacher performance appraisal system, so in this research, we will compare the SAW method with the WP method in honorary teacher performance assessment system, so that it can be seen which method is more efficient in terms of the calculation process for honorary teacher performance assessment.